2015
DOI: 10.7314/apjcp.2015.16.13.5349
|View full text |Cite
|
Sign up to set email alerts
|

Association of Knowledge and Cultural Perceptions of Malaysian Women with Delay in Diagnosis and Treatment of Breast Cancer: a Systematic Review

Abstract: Background: Breast cancer is the most common cancer and the leading cause of cancer mortality among women of all ethnic and age groups in Malaysia. Delay in seeking help for breast cancer symptoms is preventable and by identifying possible factors for delayed diagnosis, patient prognosis and survival rates could be improved. Objectives: This narrative review aimed to understand and evaluate the level of in-depth breast cancer knowledge in terms of clinical breast examination and breast self-examination, and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 24 publications
4
56
0
2
Order By: Relevance
“…Cancer is less often suspected among young patients as compared to older patients. Mammography is significantly less sensitive in detecting lesions in younger women than older women (68% vs 91%) . Fibroadenosis and fibrocystic disease are very common in young women .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer is less often suspected among young patients as compared to older patients. Mammography is significantly less sensitive in detecting lesions in younger women than older women (68% vs 91%) . Fibroadenosis and fibrocystic disease are very common in young women .…”
Section: Discussionmentioning
confidence: 99%
“…Mammography is significantly less sensitive in detecting lesions in younger women than older women (68% vs 91%) . Fibroadenosis and fibrocystic disease are very common in young women . There are serious problems in access to health services, the strength of the first level of care for the early detection of symptomatic patients, the regulation of establishments where breast imaging tests are performed, and the faulty or absent delineation of referral pathways to cancer care …”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that awareness was higher in participants of urban area than that of rural area as found in a study in Malaysia also. 25 …”
mentioning
confidence: 99%
“…In a systematic review of 42 studies by Khan and colleagues (2015) in Malaysia, limited knowledge of breast cancer caused misconceptions and delays in accessing healthcare. [16] Ten women in our study (15%) said they would visit the traditional healer first, which would delay seeking care at a health facility. In Kenya, oncologists visited traditional healers to advise that women with breast problems should be referred to physicians immediately to improve their chance of survival.…”
Section: Discussionmentioning
confidence: 85%